Seismic Damage and Analysis of the Xiker Earth Dam During the 2020 Jiashi Earthquake, Northwestern China - Yao, Yuan; Tang, Lihua; Li, Wenqian; He, Jingang; Jia, Hailiang (Frontiers in Earth Science, 2021)
The 2020 Jiashi Mw 6.0 earthquake occurred at the Kepingtage fold-and-thrust-belt in the South Tianshan front, northwestern China. The ground shaking caused extensive co-seismic deformation of the Xiker dam in the meizoseismal area. We obtained strata distribution characteristics of the dam foundation through drilling. Using laboratory and in situ tests, the particle size distribution, standard penetration, and shear wave velocity of each layer were obtained. Along with peak ground acceleration, we evaluated the potential of sand liquefaction in various layers and proposed a relationship between dam fissures and sand liquefaction. Our results suggest that sand liquefaction occurred in the silty sand layer 0–3 m beneath the dam foundation. Using numerical simulations, we found that sand liquefaction behind the dam can cause different horizontal deformation vectors in the dam foreslope and backslope, which cause the dam to rotate in the downstream direction. Large fissures also formed on the dam crest.